2009
DOI: 10.2353/ajpath.2009.080945
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Wnt Pathway Plays a Pathogenic Role in Diabetic Retinopathy in Humans and Animal Models

Abstract: Although Wnt signaling is known to mediate multiple biological and pathological processes, its association with diabetic retinopathy (DR) has not been established. Here we show that retinal levels and nuclear translocation of ␤-catenin, a key effector in the canonical Wnt pathway, were increased in humans with DR and in three DR models. Retinal levels of lowdensity lipoprotein receptor-related proteins 5 and 6, coreceptors of Wnts , were also elevated in the DR models. The high glucose-induced activation of ␤-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
189
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(203 citation statements)
references
References 50 publications
(37 reference statements)
8
189
1
1
Order By: Relevance
“…Immunohistochemistry was performed as described by Chen et al [11]. Briefly, paraffin-embedded kidney sections were stained with the antibody for β-catenin at a dilution of 1:250 for 1 h. After thorough washes with PBS, immunosignals were developed using an ABC kit (Vectastain ABC; Vector Laboratories) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Immunohistochemistry was performed as described by Chen et al [11]. Briefly, paraffin-embedded kidney sections were stained with the antibody for β-catenin at a dilution of 1:250 for 1 h. After thorough washes with PBS, immunosignals were developed using an ABC kit (Vectastain ABC; Vector Laboratories) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Care, use and treatment of all animals in this study were in strict agreement with the Guidelines for the Care and Use of Laboratory Animals set forth by the University of Oklahoma. Experimental diabetes was induced in the rats as described by Chen et al [11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, great progress has been achieved in identifying soluble factors in the circulation and vitreous fluid, such as TNF-a, VEGF, and sICAM-1, which are associated with the development and progression of DR. [2][3][4][5][6][7][8] A recent study demonstrated that the canonical Wnt signaling pathway is activated in the retina in humans with DR and in DR animal models, and it has a causative role in DR. 9 The Wnt/b-catenin signaling pathway is an important signaling pathway that regulates multiple biological and pathological processes including cell proliferation and differentiation, apoptosis, stem cell maintenance, angiogenesis, inflammation, fibrosis, and carcinogenesis. 10 This signaling pathway is regulated by a number of natural inhibitors including Dickkopf-1 (DKK-1), a well-established specific inhibitor of the Wnt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%